2018
DOI: 10.1016/j.jpdc.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of epidemic spreading on community networks with heterogeneity

Abstract: h i g h l i g h t s• A modified community network model with heterogeneity among communities is proposed.• A mathematical epidemic model for each community is presented based on this network.• Study the effect of the location of initial infection node on epidemic spreading. • Study the impact of the heterogeneity among communities on epidemic spreading. a b s t r a c t A large number of real world networks exhibit community structure, and different communities may often possess heterogeneity. In this paper, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In 1999, Barabasi and Alber [11] proposed a scale-free network model (BA). In 2018, considering the heterogeneity among communities, Li et al [12]. constructed a new community network model in which the communities showed significant differences in average degree.…”
Section: Related Workmentioning
confidence: 99%
“…In 1999, Barabasi and Alber [11] proposed a scale-free network model (BA). In 2018, considering the heterogeneity among communities, Li et al [12]. constructed a new community network model in which the communities showed significant differences in average degree.…”
Section: Related Workmentioning
confidence: 99%
“…Jean-Gabriel studied the emergence of community structures and the network model of structural evolution within communities [ 30 ]. Li and Jiang considered a disease model with community heterogeneity and found that the community heterogeneity affects the transmission threshold and disease prevalence rate [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, network models of "social contagions" predict the spread of beliefs or information through populations (28)(29)(30)(31)(32)(33). Studies focusing on specific aspects of social contact networks have shown that a variety of structural features -edge density, clustering coefficient, modularity -of those networks affect the progression of epidemics and information (34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%